Perancangan Baru Klinik Tumbuh Kembang Anak Autisme Di Surabaya Dengan Pendekatan Multy-sensory - Bella Yustisia Dewanti, Almira; Akhmadi; Haristianti, Vika (Telkom University, 2024)
Surabaya faces challenges in providing healthcare services for children with autism, particularly due to the limited availability of therapy and developmental monitoring facilities. This creates difficulties for families seeking the necessary care. The design of the Child Development Clinic in Surabaya aims to offer healthcare and therapy services, as well as monitor and evaluate the developmental progress of autistic children aged 0-12 years. The clinic is also designed to serve as a consultation and educational facility for parents, communities, and the general public regarding autism. The methodology includes primary data collection through field surveys, interviews, and documentation, along with secondary data from literature studies. The outcome of the design is the application of a multi-sensory approach, tailored to the needs of autistic children who have heightened sensitivity to environmental elements. This approach is expected to create a therapeutic environment that supports the optimal development of children with autism. Keywords: autism, children, child develompent clinic, multy-sensory